The Impact of Selected Economic Variables on New Business Formation and Business Failures - J. Kent Millington (Journal of Small Business Finance, 1994)
The current study was undertaken to identify economic variables that could be identified as influential in new business formations and failures. Monthly formations and failures for each state, summed by regions and the entire USA, as reported by Dun & Bradstreet, are used. The time period is from January, 1980 to October, 1991.
Keywords: M13; L25; L11; 650; New Business Formation; Failures; Startup